Power Quality Improvement in Distributed Generation using DSTATCOM and Photovoltaic Power Controller (International Journal of Innovative Research in Computer Science & Technology, 2019)
Conventional energy sources like coal, nuclear  energy sources, water, and other fossil fuels are getting  depleted day by day. The availability of these resources  is limited and would be exhausted one day. Therefore  people have recently started to use renewable energy  sources like sun, wind and tidal energy for electrical  power generation. The electricity generators which are  mounted within the premises of consumers or in the  vicinity of load are known as Distributed Generation  resources. One of the abundant available energy  resources is sun. The sunlight available from sun as  expected would last for millions of years. The sunlight  can be converted to electrical energy using Photovoltaics.  The PV Panels mounted on the rooftops can convert  sunlight to electrical energy. These PV panels contain  small devices called as solar cells. The PV source is also  connected to the utility grid through suitable Power  Electronic Interfaces. The PV panels are distributed  randomly in each phase. Sometimes the power from PV  source in one phase can exceed the power generated  from the grid in that phase. This excess power can flow  from the point of common coupling towards the  substation and can cause unbalance in the three phase  currents of the transmission line. This Paper outlines a  technique wherein a Distributed Static Compensator  (DSTACOM) is connected to the grid which will take the  unbalanced three phase currents of the transmission  line, process the currents and inject currents back in the  transmission line so as to make the three phase currents  balanced, thus balancing the three phase power.
Keywords: DSTATCOM; DVR; Reverse Power Flow; PV; Distributed Generation